Pelatihan Respiratory Hygiene untuk Pencegahan Penularan Penyakit Saluran Pernapasan Remaja di SMA 5 Depok - Ira Marti Ayu; Decy Situngkir; Namira Wadjir Sangadji; Rahmawati Rahmawati (Jurnal Abdimas Kesehatan (JAK), 2023)
School is one place that has a risk of transmitting respiratory disease. Many students do activities in the classroom where they contact each other frequently, closely and for a long time. If the students have respiratory disease, the risk of transmission will be higher. Therefore, training the students in respiratory hygiene in SMA N 5 Depok is essential. There were 38 students in the eleventh grade who attended the offline training. This training is carried out by delivering materials and practices related to respiratory hygiene. We delivered the material with PowerPoint and did the practice with educated games. Then, we did a pre and post-test to assess the students' knowledge. The result reveals differences in knowledge before and after conducting respiratory hygiene health training. Through this activity, students can implement the cough/sneeze procedures and handwashing practice appropriately to minimize the risk of respiratory disease transmission.